Comment on 2018 American Academy of Neurology guidelines on disease-modifying therapies in MS. (12th June 2018) - Corboy, John R.; Weinshenker, Brian G.; Wingerchuk, Dean M.
Abstract : The American Academy of Neurology has published a comprehensive review and guidelines for the use of disease-modifying therapies (DMTs) in multiple sclerosis (MS) for the first time since 2002. These guidelines represent the work of MS experts, patients, and guideline experts and are based on their review of randomized controlled trials and observational evidence that addresses a set of prespecified questions related to starting, switching, and potentially discontinuing DMTs. Many of the recommendations address decision-making regarding the use of DMTs and incorporate the perspective of patients. Modified Delphi methods were used to establish consensus recommendations that were assigned a level of clinical obligation (actions a clinician must [A], should [B], or may [C] do). Most guideline recommendations are level B. Few reached level A, and several achieved only level C, primarily because of lack of evidence. The guidelines eschew formal treatment algorithms and do not address financial considerations and a variety of other controversies. We identify remaining uncertainties, the most important of which is the choice of available DMTs for the average newly diagnosed patient. We reiterate a number of research needs identified in the guidelines that could affect the use of DMTs, including improved definition of breakthrough disease requiring change in therapy, development of better and universally accepted definitions of both benign and aggressive MS, more and longer-duration comparative effectiveness trials, discovery and validation of biomarkers of disease activity and response to therapy, and development of treatment strategies focused on neuroprotection, remyelination, and neural repair.